Development and Characterisation of an in vitro Model of Wallerian Degeneration - Elsayed, Heba; Faroni, Alessandro; Ashraf, Mohammad R.; Osuji, Judith; Wunderley, Lydia; Zhang, Ling; Elsobky, Hesham; Mansour, Mohamed; Zidan, Ashraf S.; Reid, Adam J. (Frontiers in Bioengineering and Biotechnology, 2020)
Following peripheral nerve injury, a sequence of events termed Wallerian degeneration (WD) takes place at the distal stump in order to allow the regenerating axons to grow back towards the target organs. Schwann cells (SCs) play a lead role in this by initiating the inflammatory response attracting macrophages and immune cells, as well as producing neurotrophic signals that are essential for nerve regeneration. The majority of existing research has focused on tools to improve regeneration, overlooking the critical degeneration phase. This is also due to the lack of in-vitro models recapitulating the features of in-vivo WD. In particular, to understand the initial SC response following injury, and to investigate potential interventions, a model that isolates the nerve from other systemic influences is required. Stem cell intervention has been extensively studied as a potential therapeutic intervention to augment regeneration; however, data regarding their role in WD is lacking. Thus, in this study we describe an in-vitro model using rat sciatic nerve explants degenerating up to 14 days. Characterisation of this model was performed by gene and protein expression for key markers of WD, in addition to immunohistochemical analysis and electron microscopy. We found changes in keeping with WD in-vivo: upregulation of repair program protein CJUN, downregulation of myelin protein genes and subsequent disorganization and breakdown of myelin structure. As a means of testing the effects of stem cell intervention on WD we established indirect co-cultures of human adipose-derived mesenchymal stem cells (AD-MSC) with the degenerating nerve explants. The stem cell intervention potentiated neurotrophic factors and Cjun expression. We conclude that our in-vitro model shares the main features of in-vivo WD, and we provide proof of principle on its effectiveness to study experimental approaches for nerve regeneration focused on the events happening during WD.